In Vitro Effect of Ethanol on ADP and Collagen-Induced Platelet Aggregation - Bengmark, Stig; Elmér, Olle; Göransson, Göran; Zoucas, Evita (Thrombosis and Haemostasis, 1981)
Platelet aggregation was measured by Born’s method. Plasma from Sprague-Dawley rats and inbred albino rabbits was used. 20% ethanol in 0.9%(w/v) NaCl was added to plasma at final concentrations of 56.5 mM, 85.9 mM 171.5 mM and 343.1 mM or to whole blood at final concentrations of 8.7 mM, 17.4 mM, 52.5 mM, 171.5 mM and 343.1 mM. Experiments using 0.9% NaCl volumes equivalent to the added ethanol volume were also conducted. Dose-response aggregation tests showed that a decrease in ADP-and collagen-induced aggregation existed when ethanol was mixed with rat or rabbit blood prior to the preparation of platelet-rich plasma. There was no effect on ADP-induced platelet aggregation when ethanol was mixed with rat or rabbit plasma. Collagen-induced aggregation was impaired only in rat plasma when ethanol concentration reached 343.1 mM. These results suggested that ethanol modified platelet function possibly via red cells.
Keywords: Ethanol; Platelet rich plasma; Blood; Platelet aggregation